LEVEL OF BIOSECURITY IMPLEMENTATION ON PIGS FARMS IN MELINGGIH VILLAGE, PAYANGAN DISTRICT, GIANYAR REGENCY, BALI - Ayub Andreas Andreas Panahatan Napitupulu; I Wayan Masa Tenaya; Romy Muhammad Dary Mufa (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Pig farming in Indonesia has long been recognized by society and has become a well-established industry. The demand for pork products continues to show growth, but the increased risk of animal diseases remains a factor that could hinder production development in pig farming. The aim of this study is to determine the level of biosecurity implementation in pig farming in Melinggih Village, Payangan District, Gianyar Regency. In this study, a total sampling method was used, and data were collected through close-ended questionnaires via interviews with 20 pig farmers. The results were analyzed using descriptive quantitative analysis with the Guttman scale. The data obtained from the interviews were tabulated using Microsoft Excel, and the percentage of data in accordance with the assessments was calculated. Additionally, the data were analyzed using Spearman's rank correlation test to determine the relationship between knowledge, attitudes, and practices toward the implementation of biosecurity. The results show that the level of biosecurity implementation and the level of knowledge, attitudes, and practices of pig farmers toward biosecurity implementation in Melinggih Village, Payangan District, Gianyar Regency are as follows: isolation (67%), sanitation (74%), traffic control (58%), knowledge (43%), attitude (68%), and practice (74%). Meanwhile, the relationship between knowledge, attitude, and practice toward biosecurity implementation is unidirectional and has a significant correlation strength. Based on the results of this study, it is recommended that farmers further improve their knowledge of biosecurity and maintain or optimize the existing biosecurity implementation.